Oceanic Effect on Precipitation Development in the Maritime Continent during Anomalously-Wet Dry Seasons in Java - Erma Yulihastin; Muhammad F P; Suaydhi Suaydhi; Iis Sofiati (Faculty of Geography, Universitas Gadjah Mada, 2021)
Anomalous rainfall during the dry season over the tropical region is determined by sea surface temperature (SST) anomalies driven by remote forcing. Anomalous precipitation during the dry season in Java (the so-called